THE RELATIONSHIP BETWEEN PERSONALITY PATTERNS, OBESITY AND OVERWEIGHT AMONG SAUDI WOMEN DURING THE COVID-19 PANDEMIC: A COMPARATIVE STUDY - AL-Dossary Reem Nassar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of the research is to identify the prevalence of obesity and overweight, with the personality type prevalent among a sample of Saudi women and according to the marital status and to identify the correlation between the prevalence of obesity and overweight, with the nature of the prevailing personality type and according to the social status. The sample consisted of (2923) Saudi women, of which (1345) married women made up a percentage (46.01%), (1578) unmarried girls constitute (53.98%) of the total research sample. Weight and height were measured, and BMI classifications were obtained based on WHO indicators. Then, the research sample responded to the Iznik list of personality. The results indicated an increase in the prevalence of obesity and overweight among married women compared to unmarried girls, by (53.08%), (14.72%), (32.53%), (13.37%), respectively, and it was found that there is a significant increase in the percentage of Married women with a balanced personality type at a rate of (68.84%), a decrease in their emotional personality pattern by (31.15%), an increase in the percentage of extroverted personality among them by (62.37%), and a decrease in the percentage of introverted personality by (37.62%), While it was also found that there is a decrease in the proportion of balanced personality among unmarried girls compared to married women by (55.83%), and an increase in the percentage of the emotional personality type among them by (44.16%), and it was also found that there is a decrease in the percentage of The extroverted personality type and the high percentage of the introverted personality type in proportions respectively (39.35%) and (60.64%). With regard to the relationship between obesity and personality type, it was found that the percentage of introverted personality type is lower among married women who are obese or overweight. Existence of the whale pattern the equilibrium testis, while the relationship was the opposite of that for unmarried women and those with obesity or overweight, as they had a higher incidence of introverted personality type and a lower percentage of equilibrium personality type. In light of the findings and in light of the Corona pandemic and the commitment of women at home to not be exposed to the virus and the lack of sports activities, it was possible to recommend the necessity of finding sports programs for practicing sports and physical activity for women in general, especially those unmarried women, because obesity and overweight have very negative effects on personality style. And their mental health.